2002
DOI: 10.1163/156854102760082203
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of flavipin, a fungus compound antagonistic to plant-parasitic nematodes

Abstract: An isolate of the fungus Chaetomium globosum produced culture broths that inhibited in vitro egg hatch and juvenile mobility of root-knot nematode (Meloidogyne incognita) and hatch of soybean cyst nematode (Heterodera glycines). Extraction and bioassay-directed fractionation of the culture broth ltrate determined that avipin, a low molecular weight compound, was the fungus metabolite responsible for most of the nematode-antagonistic activity. Synthesis of avipin permitted evaluation of the compound as a suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Other studies also demonstrated that fungi from the genera Acremonium, Paecilomyces, and Chaetomium produced nematicidal compounds (Sharon et al, 2001;Nitao et al, 2002;Goswamia et al, 2008), Phyllosticta Cucumber endophytic fungi strain was for the first time found to produce nematicidal compounds in our study. Toxic activities of the culture filtrates of Fusarium isolates and Trichoderma Tr882 were not detected.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Other studies also demonstrated that fungi from the genera Acremonium, Paecilomyces, and Chaetomium produced nematicidal compounds (Sharon et al, 2001;Nitao et al, 2002;Goswamia et al, 2008), Phyllosticta Cucumber endophytic fungi strain was for the first time found to produce nematicidal compounds in our study. Toxic activities of the culture filtrates of Fusarium isolates and Trichoderma Tr882 were not detected.…”
Section: Discussionsupporting
confidence: 80%
“…Endophytic Fusarium isolates were proved again to be useful candidates for plant parasitic nematode control. Fungi from the genera Acremonium, Paecilomyces, Trichoderma, and Chaetomium have been extensively documented as antagonistic to plant parasitic nematodes (Sharon et al, 2001;Nitao et al, 2002;Kalele et al, 2007;Goswamia et al, 2008). In this study, it was shown that part of their life cycle can also be endophytic.…”
Section: Discussionmentioning
confidence: 60%
“…However, their effect is quite astonishing when considering their very simple chemical structures, compound 4 even lacking a stereogenic center. A series of simple aromatic fungal compounds -including para-anisaldehyde, para-anisyl alcohol, 1-(4-methoxyphenyl)propane-1,2-diol, 2-hydroxy-(4'-methoxy)propiophenone [16], 3-para-anisoloxypropionate [17], flavipin [18], 3,5-dihydroxy-4-(3-methylbut-2-enyl)-benzene-1,2-dicarbaldehyde, and butyl 2,4-dihydroxy-6-methylbenzoate -were also found to exhibit weak-to-moderate activities against different nematodes [19].…”
mentioning
confidence: 99%
“…A closely related species, C. globosum, produced compounds that inhibited egg hatching and J2 motility in Meloidogyne incognita and egg hatch in Heterodera glycines (Nitao et al, 2002). The activity of the culture filtrate of A. strictum decreased after autoclaving.…”
Section: Discussionmentioning
confidence: 99%